2012
DOI: 10.1136/emermed-2012-201224
|View full text |Cite
|
Sign up to set email alerts
|

National audit of antidote stocking in acute hospitals in the UK

Abstract: Stocking of less commonly used antidotes is inconsistent. This is likely to result in delayed access to treatment and worse patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 17 publications
1
41
0
6
Order By: Relevance
“…There was suboptimal availability within 1 hour, of antidotes for the treatment of poisoning with glycol and alcohol. The authors observed that despite the presence of national guidelines, there was little improvement in antidote stocking and there were no studies exploring the reasons for inadequate stocking in UK [2]. In Canada, the findings were similar following the introduction of guidelines.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…There was suboptimal availability within 1 hour, of antidotes for the treatment of poisoning with glycol and alcohol. The authors observed that despite the presence of national guidelines, there was little improvement in antidote stocking and there were no studies exploring the reasons for inadequate stocking in UK [2]. In Canada, the findings were similar following the introduction of guidelines.…”
Section: Discussionsupporting
confidence: 61%
“…The questionnaire enquired on the quantities and availability of 29 antidotes of which 28 had been recommended in the 2008 College of Emergency Medicine/National Poisons Information Service (CEM/NPIS) antidote guidelines. Intralipid was added to the list by the authors of the UK national audit, as it is recommended for patients severely poisoned with local anesthetics and lipid-soluble drugs [2]. The antidotes were categorized as A (having 12 antidotes for immediate availability in the Emergency Department (ED) or any area where poisoned patients are initially treated i.e.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations